1982
DOI: 10.5547/issn0195-6574-ej-vol3-no2-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Energy Demand: The Developing Countries

Abstract: The estimation of energy demand, including conservation possibilities, is now widely recognized as a topic of major importance in both industrial and developing countries. Recent rises in oil prices and the possibility of both long- and short-term supply disruptions or shortages have focused the attention of energy planners throughout the world on how much energy might be consumed in the future, and to what extent energy consumption is sensitive to different kinds of conservation measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The central theme of the debate revolves around whether electricity consumption promotes or retards economic growth. The utilisation of modern energy in the production process, along with capital and labour, is considered as a pre-requisite for social, economic and technological progress (see Dunkerley, 1982;Ebohon, 1996;Templet, 1999). The researchers, who are in support of the above-mentioned hypothesis, confirmed that, without energy, economic growth and technological progress will be unachievable.…”
Section: Introductionmentioning
confidence: 98%
“…The central theme of the debate revolves around whether electricity consumption promotes or retards economic growth. The utilisation of modern energy in the production process, along with capital and labour, is considered as a pre-requisite for social, economic and technological progress (see Dunkerley, 1982;Ebohon, 1996;Templet, 1999). The researchers, who are in support of the above-mentioned hypothesis, confirmed that, without energy, economic growth and technological progress will be unachievable.…”
Section: Introductionmentioning
confidence: 98%
“…Thus similar to the Lee study, we consider a trivariate model but one that proxies energy prices. This is because price responses have been argued to have a crucial role in affecting income and energy consumption directly (Dunkerley, 1982;Hoa, 1993). Although data on energy prices would be ideal to use, given the multicountry nature in a panel estimation framework, it is not possible to obtain a comparable series on energy prices for all 20 countries over 1971-2002.…”
Section: Introductionmentioning
confidence: 99%
“…1977;as cited in Zilberfarb and Adams, 1981;Akarca and Long, 1980;Nguyen. 1984;Yu and Hwang, 1984;Ang, 1987) and developing countries (Zilberfarb and Adams, 1981;Dunkerley, 1982;Desai, 1986;Ang, 1987) have attempted to verify this hypothesis. The major conclusion' of these studies is that income elasticities in developed countries declined from above unity to below one in the post-1973 period, and at the same time were lower than those obtained for developing countries.…”
Section: Energy Consumption and Economic Growthmentioning
confidence: 99%
“…See Dunkerley (1982). Desai (1986) and Pearson (1987) for detailed income elasticity estimates for developing countries; and Akarca and Long (1980) and Nguyen (1984) for estimates for developed countries.…”
Section: Saps In Africa Emphasized Institutional Reforms In the Fomentioning
confidence: 99%